Differences in trauma-informed care implementation by clinic-level factors across Ryan White HIV clinics in the Southeastern United States. Issue 2 (1st February 2023) - Kalokhe, Ameeta S.; Adam, Elizabeth; Colasanti, Jonathan; Livingston, Melvin; Root, Chris; Sales, Jessica M.
ABSTRACT: Trauma is common among people with HIV (PWH) and associated with low HIV care engagement, thus trauma-informed care (TIC) integration within HIV services is critical. From December 2019 to April 2020, we conducted surveys with 321 administrators, providers, and staff of 46 Ryan White HIV clinics (RWCs) in 8 Southeastern U.S. states to assess level of TIC implementation and clinic-level factors associated with TIC adoption. The mean score for TIC implementation was highest for the Physical Environment domain ( μ = 4.08, SE = 0.07), followed by Screening, Assessment, and Treatment Services ( μ = 3.96, SE = 0.07), Cross-sector Collaboration ( μ = 3.75, SE = 0.08), Engagement and Involvement ( μ = 3.92, SE = 0.09); and Training and Workforce Development ( μ = 3.54, SE = 0.12). Greatest gaps were in staff TIC training, staff support, presence of onsite legal, spiritual, and housing services, and seeking patients' definitions of safety and developing their individualized crisis/safety plans. Across most TIC implementation domains, clinic type, urbanicity, academic affiliation, and presence of onsite psychosocial support services were associated with level of TIC adoption. Thus, RWCs have the necessary foundation to integrate TIC practices, but further progress will require addressing identified gaps. The overall lack of significant difference in TIC implementation across domains by clinic-level factors suggests that a RW network-wide approach to enhancing TIC integration is feasible.